2021
DOI: 10.7575/aiac.ijkss.v.9n.1p.36
|View full text |Cite
|
Sign up to set email alerts
|

Differences in External Workload Demand between Session Types and Positions in Collegiate Men’s Ice Hockey

Abstract: Background: Despite the importance of using a thorough understanding of competition demands to optimize preparatory strategies, there is a paucity of longitudinal workload data in ice hockey. Objectives: The purpose of this study was to determine differences in workload characteristics between training and matches, and assess differences between forwards and defensemen. Methods: All players from a NCAA Division I Men’s Ice Hockey Team wore Catapult S5 units for all on-ice activities for two consecutive seasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 24 publications
1
9
2
Order By: Relevance
“…Similar to distance per min, the more continuous movement and only obtaining data while the puck is in play, seems like the logical explanation for the small increase in PlayerLoad TM per min during simulation matches. When comparing PlayerLoad™ from matches, our results are lower than Neeld et al ( 2021 ) reported in collegiate level male players (total PlayerLoad TM 220–234 [DEF-FWD]) and what Douglas et al ( 2019b ) reported in two other studies in elite female players; 230–239 [DEF-FWD] and Douglas et al ( 2020 ); 228–246, [DEF-FWD]). This difference might be attributed to the methodological differences (inclusion of data), however, playing level and athlete caliber (Perez et al, 2020 ) could also contribute to the observed differences.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…Similar to distance per min, the more continuous movement and only obtaining data while the puck is in play, seems like the logical explanation for the small increase in PlayerLoad TM per min during simulation matches. When comparing PlayerLoad™ from matches, our results are lower than Neeld et al ( 2021 ) reported in collegiate level male players (total PlayerLoad TM 220–234 [DEF-FWD]) and what Douglas et al ( 2019b ) reported in two other studies in elite female players; 230–239 [DEF-FWD] and Douglas et al ( 2020 ); 228–246, [DEF-FWD]). This difference might be attributed to the methodological differences (inclusion of data), however, playing level and athlete caliber (Perez et al, 2020 ) could also contribute to the observed differences.…”
Section: Discussioncontrasting
confidence: 89%
“…Similar to distance per min, the more continuous movement and only obtaining data while the puck is in play, seems like the logical explanation for the small increase in PlayerLoad TM per min during simulation matches. When comparing PlayerLoad TM from matches, our results are lower than Neeld et al (2021) ). This difference might be attributed to the methodological differences (inclusion of data), however, playing level and athlete caliber (Perez et al, 2020) 2020)].…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…In ice hockey, this is usually done using wearable technology embedding accelerometer and heart rate (HR) or collecting the rating of perceived exertion (RPE) during practice sessions and official games. However, limited attempts have been done to describe TL measures and intensity in elite ice hockey [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%